Mycological and Mycotoxinic Investigations of Plant Substrates in the Moldavian Plateau Area - Ioana Poroșnicu; Andra S. Neculai-Văleanu; Adina M. Ariton; Nicolae I. Bădilaș; Bianca M. Mădescu; Ioana Crivei (Scientific Papers Animal Science and Biotechnologies, 2023)
Mycological and mycotoxinic contamination of plant substrates endangers the most important sectors globally - agriculture, animal husbandry and the food industry. The starting point of contamination is the spread of pathogens in the field, transport and even handling before storage. Increasing the temperature and humidity of these seeds can be an important factor in the development of fungi and mycotoxins. In this paper, we aimed to evaluate the fungal and mycotoxinic potential in the samples that characterize the area of ​​the Moldavian Plateau. From agricultural farms, samples such as corn grains, wheat, barley, soybeans, rapeseed, peas and sunflowers were collected and analyzed and a series of 10 determinations / sample were performed in order to establish the fungal and mycotoxinic load. The results clearly indicate the presence on the seed coat of fungal spores of the genera Penicillium (60%), Aspergillus (52.8%), Fusarium (48.5%) together with species from the Mucoraceae family (38.5%). The most contaminated samples were corn, wheat and barley grains. The climatic conditions in this geographical area are favorable for these species of micromycetes and regarding the mycotoxinic examination performed by the TLC technique, the mycotoxins identified in the 70 plant substrates were aflatoxins B1, G2, ochratoxin and zearalenone.